A framework for fracture assessments of dissimilar girth welds in offshore pipelines under bending. (September 2016) - Souza, R.F.; Ruggieri, Claudio; Zhang, Zhiliang
Highlights: An equivalent stress–strain curve coupled with the EPRI methodology is proposed. V-groove weld joints are analyzed using a weld bevel simplification scheme. Defect assessments of clad pipes having undermatched and partially mismatched girth welds. A verification study compares the new method with engineering codes and numerical tools. Abstract: This work describes the development of a framework for structural integrity assessments of dissimilar girth welds in clad and lined pipes subjected to high levels of bending load for a wide range of pipe geometries, crack configurations, weld grooves and weld strength mismatch levels based upon an EPRI estimation scheme for crack driving forces coupled with a weld groove simplification procedure and the equivalent stress–strain relationship. Systematic validation of the method is provided and the crack driving force estimation accuracy is demonstrated through comparisons with numerical tools and 3-D finite element analyses for reeled pipelines.